Factors Affecting the Degree of Staffing Autonomy in Vietnamese Public Universities: An Exploratory Study from Civil Servants’ Perspectives - Duong, Nguyen Thi Thuy; Hoa, Ngo Huong (Pancasila International Journal of Applied Social Science, 2026)
This study explores the factors influencing the degree of staffing autonomy in Vietnamese public universities from the perspectives of civil servants (including academic staff, administrative professionals, and university managers). A quantitative cross-sectional survey was conducted with 286 respondents from 12 public universities across Northern, Central, and Southern Vietnam. The questionnaire used a five-point Likert scale. Data were analyzed using SPSS 26.0 through Cronbach’s Alpha reliability testing, Exploratory Factor Analysis (EFA), Pearson correlation, and Multiple Linear Regression (MLR). The EFA identified five factors affecting staffing autonomy: (1) Financial Self-Sufficiency (FSS), (2) Institutional Legal Framework (ILF), (3) Internal Governance Capacity (IGC), (4) University Council Effectiveness (UCE), and (5) Organizational Culture of Change (OCC). The regression model explained 62.4% of the variance (Adjusted R² = 0.624). Financial Self-Sufficiency emerged as the strongest predictor (β = 0.312), followed by Institutional Legal Framework (β = 0.258), Internal Governance Capacity (β = 0.214), University Council Effectiveness (β = 0.176), and Organizational Culture of Change (β = 0.134). An independent samples t-test revealed significant differences in perceived staffing autonomy between financially self-sufficient and partially state-funded universities. This is among the first large-scale, multi-institutional quantitative studies on staffing autonomy in Vietnamese higher education that surveys civil servants across occupational categories. The findings provide empirical evidence for policymakers and university administrators to prioritize financial self-sufficiency and legal reform as preconditions for effective human resource autonomy.